Feasibility of a standardized family participation programme in the intensive care unit: A pilot survey study - Boukje Dijkstra; Lucia Uit het Broek; Johannes van derHoeven; Lisette Schoonhoven; Frank Bosch; Marijke Van der Steen; Paul Rood; Lilian Vloet (Wiley, 2023)
Abstract Aim To assess the feasibility and applicability of a standardized programme to facilitate family participation in essential care activities in the intensive care unit. Design Pilot study with a cross‐sectional survey design. Methods A standardized programme to facilitate family participation in essential nursing care activities was implemented in intensive care units of three hospitals in the Netherlands from November 2018 until March 2019. The feasibility and applicability of the programme were assessed with surveys of the patients, relatives and healthcare providers. Results Three intensive care units successfully implemented the standardized programme. Three patients, ten relatives and 37 healthcare providers responded to the surveys. Patients appreciated family participation and recognized that their relatives liked to participate. Relatives appreciated being able to do something for the patient (80%) and to participate in essential care activities (60%). The majority of relatives (60%) felt they had sufficient knowledge and skills to participate and did not feel obliged nor uncomfortable. Healthcare providers felt they were trained adequately and motivated to apply family participation; application was perceived as easy, clear and relatively effortless according to the majority. According to 68% of the healthcare providers, most relatives were perceived to be capable of learning to participate in essential care activities. Some healthcare providers felt uncertain about the patient's wishes regarding family participation, with some indicating the behaviours of relatives and patients discouraged them from offering family participation. Use of a standardized programme to facilitate family participation in essential care activities in the intensive care unit seems feasible and applicable as determined by relatives and healthcare providers.